Analisis Kredibilitas Dan Tanggung Jawab Auditor Pemerintah Dalam Pendeteksian Fraud Pada Laporan Keuangan Provinsi Sumatera Utara - Linda Wahyu Marpaung; Widia Astuty; Eka Nurmala Sari (Mahesa Research Center, 2023)
The purpose of this study is to analyze and test the effect of auditor credibility on the process of detecting fraud in financial statements and the effect of auditor responsibility on the process of detecting fraud in the financial statements of North Sumatra Province. The research method used is explorative qualitative with inductive data analysis and the research results emphasize meaning rather than generalization. This research is explorative qualitative in nature because the research that the researchers conducted aims to provide an overview of the audit process at the inspectorate of North Sumatra Province so that a narrative is obtained to reach a conclusion. The results of the study are that the inspectorate auditor has sufficient credibility and experience in examinations, the data found and recommended for North Sumatra Province for the 2013 to 2017 period there were 1,423 findings and 1,709 recommendations. With details of cases completed as many as 1,197. In the process as many as 142 recommendations and 344 have not been followed up. Then for Regencies/Cities 1,668 findings and 2,040 recommendations. Examination The auditor carries out his responsibility to detect fraud, conducts inspections in accordance with procedures and after carrying out the inspection, provides feedback by conducting formal correspondence procedures soliciting responses from the object being examined.